Psoas Muscle Index Can Be Used to Predict Long-Term Mortality in Young Male Patients With Acute-on-Chronic Liver Failure - Xu, Manman; Li, Tongzeng; Kong, Ming; Geng, Nan; Song, Wenyan; Guo, Guanya; Duan, Zhongping; Han, Ying; Chen, Yu (Frontiers in Nutrition, 2022)
Abstract Objective: The use of psoas muscle index（PMI）in acute-on-chronic liver failure (ACLF) has not been reported, and the aim of this study was to evaluate the predictive value of PMI for the prognosis of patients with ACLF. Methods: In this study, male ACLF patients who underwent abdominal CT between 2015 and 2019 in our center were included to analyze the association between PMI and 1-year mortality in male ACLF patients, and subgroup analyses were performed according to age stratification (≤ 40 and > 40 years). Results: We included 116 male patients with confirmed ACLF, with a mean PMI of 5.98 ± 1.68 cm2/m2 and a 1-year mortality of 51.7% (60). Univariate COX regression analysis showed that PMI was a protective factor [hazard ratio (HR), 0.851, 95%CI: 0.734-0.987] for 1-year mortality in male patients with ACLF. Nevertheless, multivariate analysis did not find an independent relationship between PMI and 1-year mortality. Subgroup analysis by age found that adjusted for MELD score, PMI was independently associated with 1-year mortality in young(age ≤ 40 years) male patients with ACLF (HR 0.689, 95% CI: 0.496-0.958). While no effect of PMI on 1-year mortality in non-young(age > 40 years) male ACLF patients was found. Correlation analysis found that there was no significant correlation between PMI and age in young(age ≤ 40 years) male ACLF patients, but, PMI decreased with age (r = -0.246, P < 0.05) in non-young(age > 40 years) male ACLF patients. Conclusion: PMI was found to be associated with 1-year mortality in male ACLF patients, especially in patients younger than 40 years, PMI predict 1-year mortality independent of MELD score.